Intergenerational Health Mobility in Germany - Daniel Graeber (Institute of Labor Economics (IZA), 2023)
We describe the joint permanent health distribution of parents and children in Germany using 25 years of data from the Socio-Economic Panel. We derive three main results: First, a ten percentile increase in parental permanent health is associated with a 2.3 percentile increase in their child's health. Second, employing our anchoring method, we find that a percentile point increase in permanent health ranks is associated with a 0.8% to 1.4% increase in permanent earnings. Additionally, we conclude that health is particularly important for earnings at lower levels of health.We argue that our anchoring method has great potential to enhance the comparability of the literature across data sets and countries. Third, a more favorable socioeconomic status of the parents is predominantly associated with higher upward mobility in health.
Keywords: I14; I12; J62; J13; 330; intergenerational health mobility; health measurement; inequality